Statistical Analysis of Terminal Extensions of Protein β-Strand Pairs. (28th January 2013) - Zhang, Ning; Gao, Shan; Zhang, Lei; Ruan, Jishou; Zhang, Tao
Abstract : The long-range interactions, required to the accurate predictions of tertiary structures of β -sheet-containing proteins, are still difficult to simulate. To remedy this problem and to facilitate β -sheet structure predictions, many efforts have been made by computational methods. However, known efforts on β -sheets mainly focus on interresidue contacts or amino acid partners. In this study, to go one step further, we studied β -sheets on the strand level, in which a statistical analysis was made on the terminal extensions of paired β -strands. In most cases, the two paired β -strands have different lengths, and terminal extensions exist. The terminal extensions are the extended part of the paired strands besides the common paired part. However, we found that the best pairing required a terminal alignment, and β -strands tend to pair to make bigger common parts. As a result, 96.97% of β -strand pairs have a ratio of 25% of the paired common part to the whole length. Also 94.26% and 95.98% of β -strand pairs have a ratio of 40% of the paired common part to the length of the two β -strands, respectively. Interstrand register predictions by searching interacting β -strands from several alternative offsets should comply with this rule to reduce the computational searching space to improve the performances of algorithms.